ANALISIS KEMAMPUAN METAKOGNISI SISWA MELALUI PENGGUNAAN LEMBAR KERJA SISWA BERBASIS DISCOVERY LEARNING - Amanda, Mia Hilda; Haryani, Sri; Mahamanti, F. Widhi; Marsini, Marsini (Jurnal Inovasi Pendidikan Kimia, 2020)
Chemistry learning in schools emphasizes learning chemistry concepts in a coherent, structured and detailed manner. Concepts delivered in a coherent, structured and detailed way make it easier for students to understand and understand concepts. Several strategies can be used to assist students in learning concepts, including the use of student worksheets that shape student thinking in a structured way. This descriptive analysis research aims to determine the ability of metacognition through the use of student worksheets based on discovery learning. The research design used is the One-Shot Case Study. The study was conducted by giving treatment to the group studied in the form of learning using Discovery Learning-based Student Worksheets four times. After being given treatment, the group is given a post-test in the form of questions that have metacognition indicators and question indicators, then given a questionnaire response to the worksheet based on discovery learning, a questionnaire responding to the ability of metacognition. Data from the results of the post test and questionnaire were analyzed and conclusions were drawn. The results showed an average post-test score obtained at 87.94% while the average questionnaire score obtained at 81.64%, the results of the interview analyzed descriptively also showed good metacognition skills. As for the results of students' metacognition abilities based on their ability level, they are: 17.64% low level; 61.76% moderate level; and 20.59 are at a high level. Based on the data collected, it can be concluded that the metacognition ability of the XI MIA 7 grade students of SMA Negeri 5 Purwokerto is at the most moderate level.